2011
DOI: 10.1631/jzus.b1100023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epidermal growth factor on follicle-stimulating hormone-induced proliferation of granulosa cells from chicken prehierarchical follicles

Abstract: Abstract:The development of ovarian follicular cells is controlled by multiple circulating and local hormones and factors, including follicle-stimulating hormone (FSH) and epidermal growth factor (EGF). In this study, the stagespecific effect of EGF on FSH-induced proliferation of granulosa cells was evaluated in the ovarian follicles of egg-laying chickens. Results showed that EGF and its receptor (EGFR) mRNAs displayed a high expression in granulosa cells from the prehierarchical follicles, including the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The literature on Hardy et al proved that FSH was essential for pre-antral follicle growth and function in mice (Hardy et al, 2017). In poultry, FSH treatment increased the embryonic chicken ovarian germ cell number, granulosa cells number and reduced cell apoptosis in different stage of follicles (Lin et al, 2011). In this study, the increase of FSH and LH in geese may induce follicular development and ovulation which may result in the increase of egg production of goose.…”
Section: Effects Of Vitamin E Supplementation On Serum Hormones and Gmentioning
confidence: 51%
“…The literature on Hardy et al proved that FSH was essential for pre-antral follicle growth and function in mice (Hardy et al, 2017). In poultry, FSH treatment increased the embryonic chicken ovarian germ cell number, granulosa cells number and reduced cell apoptosis in different stage of follicles (Lin et al, 2011). In this study, the increase of FSH and LH in geese may induce follicular development and ovulation which may result in the increase of egg production of goose.…”
Section: Effects Of Vitamin E Supplementation On Serum Hormones and Gmentioning
confidence: 51%
“…The only study characterizing CCND1 mRNA in bovine GC reported no change during an estrous cycle, while both CCND2 and CCND3 mRNA expression differed among phases of the estrous cycle (Shimizu et al, 2013). However, CCND1 mRNA is induced by GDF9 in human GC (Huang et al, 2009) and by EGF, FGF2 and ginsenosides in chicken GC (Tan et al, 2010; Lin et al, 2011; 2012). In endometrial tissue, FGF9 induces CCND1 (Schwartz et al, 2003; Wing et al, 2005; Chan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor (EGF) is a peptide of 53 amino acid residues, it binds to the epidermal growth factor receptor (EGFR) and initiates the cascade of intracellular signaling pathways. Therefore, EGF is involved in a variety of physiological and pathologic processes, including cell proliferation, apoptosis, migration, survival and angiogenesis (21)(22)(23). However, the potential molecular mechanisms underlying the effect of EGF on gastric cancer cell growth have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%